Management and Complications of Non-Thumb Metacarpal Fractures in the Incarcerated Population. (April 2020) - Vranis, Neil M.; Ali-Khan, Safi; Hu, Kelly; Daar, David; Bruckman, Karl; Hacquebord, Jacques
We reviewed the patient demographics, injury mechanisms, fracture characteristics, treatment modalities, and outcomes of incarcerated patients who were referred for metacarpal fracture evaluation and treatment to our high-volume tertiary care center from a New York City Department of Correction infirmary facility. There is a scarcity of information in the orthopedic and plastic surgery literature on treating these common fractures in this vulnerable population. We conducted a basic statistical analysis and discuss the potential implications of these findings. We found a high incidence of stiffness that may relate to the high rates of follow-up noncompliance coupled with prolonged immobilization. Awareness of these findings may influence treating hand specialists to use less restrictive immobilization devices such as functional bracing, elastic bandage, or neighbor strapping as an effort to promote bony union without the risk of developing stiffness and the potential to compromise general hand function when treating non-thumb metacarpal fractures.